Habits: Remaking Addiction - Fraser, Suzanne; Moore, D.; Keane, H. (Palgrave, 2014)
What is 'addiction'? What does it say about us, our social arrangements and our political preoccupations? Where is it going as an idea and what is at stake in its ongoing production? Drawing on ethnographic research, interviews and media and policy texts, this book traces the remaking of addiction in contemporary Western societies.